Aqueously soluble semi‐aromatic copolyamides with dual‐functional groups as sizing agent. Issue 9 (16th October 2018) - Qi, X.; Wang, W.; Zhang, J.; Yan, C.; Zhu, Y.; Zhang, F.
ABSTRACT: A series of novel aqueously soluble semi‐aromatic (co)polyamides, poly[(ethylenedioxy)bis(ethylene) terephthalamide]‐ ran ‐poly[(ethylenedioxy)bis(ethylene) (2, 5‐dihydroxy‐3, 6‐diallyl)terephthalamide] (CRPAOT‐x), were prepared via the solid‐state Claisen rearrangement reaction of poly[(ethylenedioxy)bis(ethylene) terephthalamide]‐ ran ‐poly[(ethylenedioxy)bis(ethylene) 2, 5‐bis(allyloxy)terephthalamide] (APAOT‐x), where x (= 0, 13, 25, 50, 75, and 100) represents the molar fraction of allyloxy containing unit. APAOT‐x was obtained through the interfacial copolymerization of terephthaloyl chloride, 2, 5‐bis(allyloxy)terephthaloyl chloride, and 2, 2′‐(ethylenedioxy)bis(ethylamine). The reaction conditions including reactant concentration, temperature, and solvent were optimized. The chemical structures of the target (co)polyamides and their precursors were characterized by proton nuclear magnetic resonance ( 1 H NMR) and Fourier transform infrared spectroscopies. The incorporation of hydrophilic (ethylenedioxy)bis(ethylene) units greatly improved the polymer solubility. CRPAOT‐x dissolved not only in polar organic solvents such as dimethylformamide, dimethyl sulfoxide, and N‐methyl pyrrolidone but also in ammonia water. Due to the presence of hydroxyl groups and oxygen‐rich aliphatic units, CRPAOT‐x showed excellent affinity toward epoxy resins. The microbond test indicated that the aramid fibers sized by these dual‐functional polymers exhibited remarkably enhanced interfacial shear strength in epoxy matrices. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47132. Abstract : A series of semi‐aromatic (co)polyamides with much improved solubility in both organic and basic aqueous solvents were prepared. The factors influencing the interfacial polymerization were carefully studied. The potential application of CRPAOT‐x serving as the sizing agents was evaluated by microbond test and inter‐laminar shear test, showing a maximum increase of 101% in IFSS. The aqueous sizing condition provided a promising perspective for the future industrial achievement.